2008
DOI: 10.1002/mrm.21528
|View full text |Cite
|
Sign up to set email alerts
|

Observation of microscopic diffusion anisotropy in the spinal cord using double‐pulsed gradient spin echo MRI

Abstract: A double-pulsed gradient spin echo (d-PGSE) filtered MRI sequence is proposed to detect microscopic diffusion anisotropy in heterogeneous specimen. The technique was developed, in particular, to characterize local microscopic anisotropy in specimens that are macroscopically isotropic, such as gray matter. In such samples, diffusion tensor MRI (DTI) produces an isotropic or nearly isotropic diffusion tensor despite the fact that the medium may be anisotropic at a microscopic length scale. Key words: MRI; double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 18 publications
(28 reference statements)
5
74
0
Order By: Relevance
“…This approach becomes ambiguous for more complex materials where several mechanisms could give the same signal attenuation. More recently, the microscopic anisotropy is detected in double-PGSE experiments by diffusion encoding in two separate time periods [26], giving characteristic signal modulations for data obtained with collinear and orthogonal displacement encoding [27][28][29] or when systematically varying the angle between the directions of displacement encoding [26,30,31]. A double-PGSE scheme to quantify microscopic anisotropy in terms of compartment eccentricity, independent of the macroscopic anisotropy, has recently been suggested [32].…”
Section: Introductionmentioning
confidence: 99%
“…This approach becomes ambiguous for more complex materials where several mechanisms could give the same signal attenuation. More recently, the microscopic anisotropy is detected in double-PGSE experiments by diffusion encoding in two separate time periods [26], giving characteristic signal modulations for data obtained with collinear and orthogonal displacement encoding [27][28][29] or when systematically varying the angle between the directions of displacement encoding [26,30,31]. A double-PGSE scheme to quantify microscopic anisotropy in terms of compartment eccentricity, independent of the macroscopic anisotropy, has recently been suggested [32].…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for any geometry with restricted diffusion. Potential applications of this theoretical work include the measurement of the size of microscopic structures in biological tissue, as for example done in (13)(14)(15).In the present work, the theory (12) has been successfully applied to quantify the apparent cell radius in an NMR imaging experiment of biological tissue. Furthermore, it has been investigated how deviations from the idealized assumptions affect the apparent radius.…”
mentioning
confidence: 95%
“…The same is true for any geometry with restricted diffusion. Potential applications of this theoretical work include the measurement of the size of microscopic structures in biological tissue, as for example done in (13)(14)(15).…”
mentioning
confidence: 99%
“…22 Also, combinations of double PGSE and image acquisition have also been reported. 23 The novelty of the work from Komlosh et al is that they experimentally demonstrated that the microscopic anisotropy of macroscopically isotropic sample, which is not accessible with conventional single direction PGSE method, can be detected at low q regime using double PGSE. Such techniques may be useful for studying porous media and biological tissues, such as tendons 24,25 and brain gray matter with potential clinical applications because of its sensitivity in the low q regime compatible with clinically available gradient strength.…”
Section: B Multiple Diffusion Nmr Scattering Experimentsmentioning
confidence: 99%
“…Such techniques may be useful for studying porous media and biological tissues, such as tendons 24,25 and brain gray matter with potential clinical applications because of its sensitivity in the low q regime compatible with clinically available gradient strength. 23 …”
Section: B Multiple Diffusion Nmr Scattering Experimentsmentioning
confidence: 99%